Between Secularist and Jihadist Bodes, Egypt and Sudan in Crossroads - Mahmoud, Mahgoub El-Tigani (European Scientific Journal, ESJ, 2016)
The societal conflicts between Secularist groups and Jihadist militants on the role religious orientations played in the state democratization, social justice, human rights, and population development posited national exigencies un-decisively met by governments of the African and Arab regions. Part one of our research theorized three typologies shaping the challenges of similar conflicts in the Arab-African states of Egypt and Sudan. The typologies symbolized a Sufi culture perpetuating Muslims’ humanitarian relations; Secularist thought excluding the politics of faith; and Jihadist reactionaries manipulating symbolic representation of religion in the striving for power domains. Lacking in serenity the Sufi culture maintained for ages by popular prevalence, the Jihadist reactionaries sponsored a theocratic militancy that generated instability by excessive violence. Entrenched in non-democratic authoritative systems, the state failed in both countries to end peacefully the deepened tensions of the ongoing contradictions. Preserving the popular culture and supporting democratic governance, the Sufi/Secularist groups would probably continue to resist the theocratic dogma that evidently penetrated the region. Part two of the research proposed a study on the typologies’ dynamics to project the extent of political integrity in the future of Sudan and Egypt. This paper comprised a brief summary of part one of the analysis.